Training on the Use of Aizuchi in Japanese Conversation (Kaiwa) for Students of SMK Antartika 2 Sidoarjo - Roni, Roni; Pratita, Ina Ika; Prasetyo, Joko; Parastuti, Parastuti; Amri, Miftachul (ABISATYA : Journal of Community Engagement, 2025)
This community service program aimed to enhance the Japanese conversation skills of students at SMK Antartika 2 Sidoarjo (Antartika 2 Vocational School in Sidoarjo) by providing training in the use of aizuchi in kaiwa (conversation). The training was conducted in a workshop format involving material presentation, conversation demonstrations, group practice, and student presentations. Evaluation results showed a significant improvement in students’ understanding of aizuchi, from 25% before the training to 100% after. Moreover, students expressed high enthusiasm to participate in similar activities in the future. The applied training model was found to be engaging and well-suited to the students’ learning styles. This activity is expected to serve as a starting point in fostering students’ interest in learning Japanese language and culture.